Cultural Diversity and its Impact on Societal Security from the Perspective of Emirates youth - Al Suwaidi, Suaad Mohammed; Alomosh, Ahmad Falah (Al-Adab Journal, 2022)
The aim of this study was to identify cultural diversity and its impact on societal security from the perspective of young Emirates youth and to recognize the economic, social, cultural, and security effects of cultural diversity. For the purpose of this study, a questionnaire was administered as a research instrument to collate data from members of the study sample consisting of 380 Emirates youth males and females, who were selected among the study population following the non-probability purposive sampling technique from members of the study population. The study concluded that from the perspective of Emirates youth, cultural diversity has serious adverse economic effects on the Emirati community and average social, cultural, and security effects. Further, the study showed that there were no statistically significant differences attributed to gender in the Emirates youth’ tendencies towards the impact of cultural diversity on community security. Based on the results, the research recommended that action be taken to raise the awareness of young Emirates youth on the value and importance of diversity and multiculturalism as a power factor and added value when properly harnessed and improved, and it encouraged the involvement in various employment sectors for effective economic contribution.